La acción de nulidad ante el Tribunal de Justicia de la Comunidad Andina - Gómez Apac, Hugo; Sauñe Torres, Amparo (Revista de Derecho, 2020)
This paper exposes the nature and scope of the action for annulment (or nullity action) which is brought before the Court of Justice of the Andean Community, in order to publicize its operation and importance as an instrument that controls of legality of the rules and acts that could contravene the Andean Community law. The methodology involved the revision of rules and standards, jurisprudence and doc-trine relating to the action for annulment which is brought before the Court of Justice of the Andean Community.